Efektivitas Daun Katuk Terhadap Produksi ASI Pada Ibu Nifas - Dina Julia; Marsasi, Bina; Magumi, Novita; Qurandini, Dalinur (STIKes Budi Mulia Sriwijaya, 2025)
Breast milk production involves the hormones prolactin and oxytocin. Where the hormones prolactin and oxytocin play an important role in breast milk production. If the mother's breast milk production is not sufficient, then the breast milk given to the baby will not be sufficient and can affect the baby's growth and development. Foods such as vegetables can increase the adequacy of breast milk production, such as katuk leaves and long bean leaves, where the content of katuk leaves such as lactagogum can increase and facilitate breast milk production. This study aims to determine the difference in the smoothness of breast milk production in postpartum mothers who breastfeed at the Dr. Sunedi Clinic, Palembang. This study uses (quasi-experimental) with a two-group pre-test and post-test research design. The sample in this study were 5 respondents given katuk leaves and 5 respondents not given katuk leaves. Based on the results of the t-test, the p-value obtained in the group given katuk leaves was 0.002 (<0.05) and in the group not given katuk leaves, the p-value obtained was 0.006 (<0.05). This shows that breast milk production in the katuk leaf group experienced a higher increase than the group not given katuk leaves. The conclusion is that Ha is accepted and Ho is rejected because the p-value is <0.05, which means there is a difference in the administration of katuk leaves on breast milk production in postpartum mothers at the Sunedi Clinic, Palembang.